PENINGKATAN KUALITAS PEMANTAUAN TUMBUH KEMBANG BALITA STUNTING MELALUI PENGEMBANGAN POS PAUD PROGRAM HOLISTIK INTEGRATIF - yuningsih (LPPM Universitas dr. Soebandi, 2026)
Stunting is a public health problem that affects not only the physical growth of toddlers but also their cognitive development, susceptibility to infections, and the quality of human resources in the future. This issue is also found in the working area of Kaliwates Health Center, Jember Regency, where monitoring of child growth and development is still not optimal due to services being more focused on physical aspects, limited knowledge and skills among community health cadres, PAUD (early childhood education) teachers, and parents, as well as inadequate SDIDTK (Stimulation, Detection, and Early Intervention of Child Growth and Development) facilities. This community service activity aims to improve the quality of monitoring the growth and development of stunted toddlers through the development of a holistic integrative PAUD post. The implementation method consists of preparation, execution, and evaluation stages using a participatory approach, including discussions, consultations, workshops, training, hands-on practice using SDIDTK tools, as well as nutrition and sanitation education. Evaluation was conducted using pre-test and post-test on 30 participants, analyzed with a paired t-test. The results showed a significant improvement in participants’ knowledge and skills after the intervention, along with strengthened capacity of cadres, PAUD teachers, and parents, availability of SDIDTK tools, and improved coordination among posyandu (integrated health posts), PAUD, and Bina Keluarga Balita (family development program for toddlers) in delivering more integrated services. Therefore, the development of a holistic integrative PAUD post is effective in improving the quality of monitoring growth and development of stunted toddlers in the working area of Kaliwates Health Center